MIXED GERM CELL-SEX CORD-STROMAL TUMORS - Lintong, Poppy M. (Jurnal Biomedik : JBM, 2012)
Abstract: The term mixed germ cell sex-cord-stromal tumors is used for a mixed tumor containing mixed germ cells and sex-cord-stromal tumors. In pathology, this is an unusual phenomenon because although the tumor has several components, the histopathologic feature is still as a single unit. The most frequent form of mixed germ cell and sex-cord-stromal tumors is gonadoblastoma. This tumor usuallly occurs in sexual development abnormality, and can be found either in ovarium or testis. The basic microscopic features of this tumor are a mixture of dysgerminoma-like primitive germinal cells, and granulosa and immature Sertoli like cells of the sex-cord-stromal tumor. Besides gonadoblastoma, there is an unclassified tumor consisting of mixed germ cells and sex-cord-stromal tumor which cover all tumors containing a mixture of germinal cells and sex-cords but its cellular characteristics differ from gonadoblastoma. Keywords: mixed germ cell, sex cord-stromal tumors, gonadoblastoma.   Abstrak: Istilah mixed germ cell - sex cord-stromal tumors sering digunakan untuk tumor campuran mixed germ cell dan sex cord-stromal tumors. Dalam bidang patologi hal ini merupakan suatu fenomena luar biasa karena  meskipun terdapat beberapa komponen tumor  namun tetap memberikan gambaran histopatologik sebagai suatu kesatuan tunggal. Bentuk paling sering dari mixed germ cell - sex cord-stromal tumors ialah gonadoblastoma. Gonadoblastoma sering ditemukan pada individu dengan perilaku seksual tidak normal. Selain pada ovarium, tumor ini juga dapat ditemukan pada testis. Gambaran mikroskopik yang mendasar dari tumor ini ialah campuran dari sel-sel germinal primitif menyerupai disgerminoma dan sel stroma sex-cord menyerupai sel-sel granulosa dan sertoli imatur. Selain gonadoblastoma, juga terdapat mixed germ cell - sex cord-stromal tumors unclassified yang mencakup semua tumor yang mengandung campuran bermacam-macam sel germinal dan sex-cord namun karakteristik selulernya tidak  serupa dengan gonadoblastoma. Kata kunci: mixed germ cell, sex cord-stromal tumors, gonadoblastomsa.